"This ain't a ghetto class; this is a fine class!": dramatic oral reading fluency activities in the social context of a ninth-grade classroom - Goering, Christian Z. (Kansas State University, 2007)
The purpose of this study was to determine what social factors influenced ninth-grade students asked to participate in dramatic oral reading activities in the context of their high school English classroom. Participatory action research was completed in cooperation with a classroom teacher and his student teacher. A grounded theory design advised the transcription, coding, and data analysis of the study. In 2006, the National Endowment for the Arts and the Poetry Foundation formed Poetry Out Loud, a National Recitation Contest where high school students around the country recited poetry in a contest form. This study used materials and some curriculum from Poetry Out Loud, but rather than memorizing and reciting the poems, the students were asked to perform dramatic oral readings of them. This focus on reading stemmed, in part, from studies completed by Rasinski (2005) claiming ninth-grade students still lacked fluency in their reading in addition to work in the areas of Automaticity (LaBerge & Samuels, 1974) and Prosody (Schreiber, 1991). These students participated in six weeks of activities designed to build skill in dramatic oral reading. Field notes were taken throughout the project. Performances were recorded using video and audio devices, student interviews were recorded and transcribed, and teacher interviews were recorded and transcribed. Data revealed fourteen categories during the open coding stage that contributed, through axial coding, to three different themes: family versus dysfunctional family, positive performance conditions versus adverse performance conditions, and literate identity versus anti-literate identity. These three themes and each respective antithesis were progressively contingent on each other when laid out in a lateral manner with the results of the project being that students either developed a literate identity when the conditions were in place or developed a decidedly anti-literate identity. This theory, grounded entirely in data collected during the study, provided an understanding of the social context at play in this classroom. This study provided qualitative insight necessary for continuing to explore dramatic oral reading fluency at the high school level by revealing the importance of community in asking students to perform in front of their peers, a potentially socially jeopardizing situation.
Keywords: Poetry out loud; Dramatic oral reading; Secondary English education; Fluency; Adolescent literacy; Classroom climate; Education, Curriculum and Instruction (0727); Education, Reading (0535)